Development of anti-asthma drugs - Buckle, Derek R.; Smith, Harry, 1921-2011 (Butterworths, 1984)
Development of Anti-Asthma Drugs reviews existing asthma treatments and novel approaches currently under investigation, in the context of their mode of action and clinical effectiveness, in the hope that this might lead to a greater understanding of the factors involved in the expression of the disease and, therefore, in the design of better drugs. It is planned based on the concept of the causes and treatment of asthma, This book is organized in three main parts. Part I deals with the nature of asthma, its pathological mechanisms, natural history and epidemiology. Part II discusses mediators.